Controlling the Output Voltage of a Step Up-Down Five-Level Inverter - Leonardus Heru Pratomo; Slamet Riyadi; Agengkarunia Cahyadi Wibawa (Jurusan Teknik Elektro, Fakultas Teknik, Universitas Negeri Semarang, 2023)
The increasing demand for electrical energy must be balanced with using renewable energy. However, the use of renewable energy requires a system to maximize the conversion of renewable energy into electrical energy. Various topologies have been studied to achieve maximum energy conversion. Two types of inverters, namely step up-down, have been widely used but have their respective limitations. Step-down inverters can only be used in lower output voltage than input voltage conditions with simple control, while step-up inverters can only operate in higher output voltage than input voltage conditions. This paper aims to combine these two converters to have both step-up-down voltage functions, with the goal of expanding the operating range and maintaining the advantages of each type. Thus, a topology called a step-up-down five-level inverter with a simple voltage-controlled capacitor balancing system is proposed in this paper. Finally, the simulation and laboratory tests were done. This inverter operates in step-up-down voltage, and the voltage in capacitors is always balanced to reach the desired level. The voltage control was done to get the constant voltage event the load was changed.